Security Council Power to Defer Investigation or Prosecution - Abdul-Jabbar, Saja Jawad; Al-Okour, Omar Saleh (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: This study, as stated in the introduction and the first two chapters, aims to clarify the nature of the power of deferral granted to the UN Security Council, its conditions, scope, and the consequences of suspending investigations or prosecutions before the International Criminal Court. Methods: The study employs several methodologies, including the descriptive-analytical approach, which begins with describing the case under study in terms of explaining the concept of postponement as a power granted to the Security Council, explaining its conditions and the most important effects of its use. Results: The exercise of the power of deferral by the UN Security Council leads to the suspension of all activities of the International Criminal Court, thereby compromising its independence and rendering it paralyzed during the deferral period and its renewal. This can result in the loss and destruction of evidence, and it impacts the rights of victims and defendants. Conclusion: The study stresses the necessity of making necessary amendments to the Charter of the United Nations and the Statute of the International Criminal Court to restore the balance between the interest of maintaining international peace and security and achieving international criminal justice while preventing impunity.